Esoteric Islam in Modern French Thought: Massignon, Corbin, Jambet - Elmarsafy, Ziad (New Directions in Religion and Literature Ser., 2021)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Contents -- Acknowledgements -- Abbreviations, Transliterations and Translations -- Introducing the Guest -- 1 Louis Massignon: In the Beginning Was Desire1 -- Truth: Visitation and Expression -- Desire as Alpha and Omega -- Language and Hospitality -- From Anā al- H˙aqq to Satyagraha -- Witness and Human Rights -- Conclusion -- 2 Henry Corbin: A Certain Vision -- Corbin Translates Heidegger -- Lessons in Vision -- Visionary Hermeneutics I: Initiations -- Visionary Hermeneutics II: Spiritual Chivalry -- 3 Christian Jambet's Resurrections -- Beginnings -- Alamūt -- Making It Last: Mullā S.adrā -- Conclusion -- EPILOGUE On Being True to Oneself: Esoteric Authenticities -- Bibliography -- Index.